KOMBINASI SENAM KAKI DAN RENDAM AIR HANGAT JAHE PADA KADAR GLUKOSA DARAH PASIEN DIABETES MELLITUS - Mohammad Tony Ashfyan; Nur Melizza (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood glucose levels and a risk of various complications, thus requiring proper management. In addition to pharmacological therapy, non-pharmacological interventions such as foot exercises and warm water soaking with ginger can be used to help control blood glucose levels and improve peripheral circulation. Objective: To determine the effect of the combination of foot exercises and warm water soaking with ginger on changes in blood glucose levels in patients with Diabetes Mellitus. Methods: This study used a case study design with a one-subject pre–post intervention approach. The subject was a patient with Diabetes Mellitus. The intervention consisted of foot exercises and warm water soaking with ginger, administered routinely for seven days. Blood glucose levels were evaluated on day 1, day 3, and day 7. Results: Blood glucose levels remained high on day 1 and day 3 but decreased on day 7, although they had not yet reached normal levels. In addition, the patient reported increased comfort, reduced tension in the lower extremities, and improved peripheral circulation. Conclusion: The combination of foot exercises and warm water soaking with ginger has the potential to be a complementary therapy in helping to reduce blood glucose levels in patients with Diabetes Mellitus, but it still needs to be combined with medical therapy and a healthy lifestyle.